Evaluation of quality of life in dogs with atopic dermatitis and their owners after lokivetmab therapy (Research, Society and Development, 2021)
Canine atopic dermatitis is an inflammatory and pruritic skin disease, with clinical characteristics associated with IgE antibodies, most commonly directed against environmental allergens which impact the quality of life in affected animals and their owners. Treatment is multifaceted and must be adapted to each patient individually. Currently, a medication based on caninized monoclonal antibody (mAb), called lokivetmab, has shown promise for controlling the signs of the disease, as it neutralizes interleukin IL-31, a cytokine that plays an important role in the pathogenesis of atopy. The impact of dermatological diseases in the life of the dog and its owner has only been studied in recent years through validated questionnaires. This additional measurement tool is important for evaluating the therapeutic success of interventions in atopic dermatitis, as clinical improvement may not correlate with an increased quality of life. This study aimed to evaluate the quality of life in dogs with atopic dermatitis and their owners after lokivetmab therapy. Ten atopic dogs treated at the dermatology service of the Veterinary Hospital of the Veterinary School from UFMG were selected. Quality of life was assessed using a validated questionnaire, before and after lokivetmab therapy. It concludes that treatment with lokivetmab significantly improved the quality of life of dogs with atopic dermatitis and their owners.